STRATEGIC ALLIANCES ON THE SUSTAINABILITY OF SMALL AND MEDIUM ENTERPRISES (SMES) IN RIVERS STATE - Wegwu, Macaulay Enyindah (American Journals, 2024)
This study investigates the impact of strategic alliances on the sustainability of Small and Medium Enterprises (SMEs) in Rivers State, Nigeria. The SMEs face a myriad of challenges such as inadequate funding, insufficient managerial expertise, leveraging shared resources, knowledge, and methods which threatens their sustainability and growth. It was in view of these aforementioned problems that necessitated this research in order to proffer solutions for SMEs to achieve sustainability and enhance growth. In solving these problems, the research involved statement and analysis of four hypotheses. Using a sample of 250 respondents randomly selected from ten SMEs, the research examines the relationships between strategic alignment, resource sharing, operational efficiency, and market expansion. The data were analyzed using the Spearman rank-order correlation coefficient. The findings reveal that both strategic alignment and resource sharing significantly contribute to operational efficiency and market expansion of SMEs. The study concludes that fostering strategic alliances is essential for enhancing the sustainability and growth of SMEs in the region. Recommendations for SMEs and policymakers are provided to facilitate effective strategic partnerships and resource sharing.
Keywords: Strategic Alliances, SMEs, Sustainability, Strategic Alignment, Resource Sharing, Operational Efficiency, Market Expansion, Rivers State